Potential der Kontrastmittel- und Dosisreduktion durch ein Dual-Source CT der 3. Generation im Vergleich zu einem Dual-Source CT der 1. Generation und Analyse der ökonomischen Rentabilität - Varli, Yossarian; Justus Liebig University Giessen (My University, 2020)
Introduction New computer tomographs, such as the 3rd generation dual-source CTs, promise a reduction of the radiation dose and the quantity of required contrast media with improved image quality. The aim of this study is to investigate whether this improvement can be achieved in common clinical practice and whether the purchase of such a computer tomograph is financially worthwhile. Technology 3rd generation dual-source CTs feature many technical improvements. High rotation and acquisition speeds enable examinations without respiratory motion artifacts and motion artifacts in general. New, powerful X-ray tubes allow high currents at low voltages, while the tube voltage can be varied between 70 and 150 kV. The focal spot of the new X-ray tubes is very small and maintains its size, which increases the image quality. Double tin filters in front of the X-ray tube improve the X-ray spectrum. Recent detectors with 3D collimators show less electronic noise and are equipped with two-dimensional antiscatter grids. And finally, a new, model-based technology is used for iterative image reconstruction. Material and Methods As part of this study at the University Hospital Giessen, all patients examined within one month on a dual-source CT of the 1st generation (CT Definition, Siemens, Erlangen) were compared with all patients examined within the same month in the following year on a dual-source CT of the 3rd generation (CT Somatom Force, Siemens, Erlangen). The aim was to show a possible reduction in radiation dose and a saving of intravenously applied, iodine-containing contrast media on the 3rd generation dual-source CT. Regarding radiation exposure, 366 examinations (DSCT 1st gen.) were compared with 370 examinations (DSCT 3rd gen.). Regarding the quantity of contrast media, 237 examinations (DSCT 1st gen.) were compared with 233 examinations (DSCT 3rd gen.). The changes were examined for their value of significance, indicated by the variable p, using the Mann-Whitney-test. Results The study reveals, using a 3rd generation dual-source CT, reduces the radiation dose (DLP) by 57.45% (p <0.0001) and the quantity of intravenously applied contrast media by 33.34% (p < 0.0001), compared to a 1st generation dual-source CT. As a representative, the average DLP of the largest comparison group CT strain standard on the 3rd generation dual-source CT is 621.04 (9.32 mSv; 79 examinations) and on the 1st generation dual-source CT 1249.84 (18.75 mSv; 101 examinations). This matches a reduction of 50.31% (p <0.0001). The average quantity of contrast media in this group is 61.67 ml for the 3rd generation dual-source CT and 98.16 ml for the 1st generation dual-source CT. This matches a reduction of 37.17% (p < 0.0001). Image quality and the informative value on the 3rd generation dual-source CT are at least the same, and in most cases better than on the 1st generation dual-source CT. Discussion 3rd generation dual-source CTs help to improve diagnosis, treatment and healing, and at the same time minimize the risk of (stochastic) radiation damage or contrast media-induced kidney damage. Especially young patients and patients with renal insufficiency benefit from these devices. Further improvements include, for example, the reduction of motion and respiratory motion artifacts or the examination of children without sedation. The advantages of the new CT machines outweigh and make them profitable. By reducing the quantity of contrast media, the costs can also be reduced. Very low dose values for native CT thorax scans may make conventional thorax images unnecessary in the future and CT thorax scans may be interesting for screening procedures. Conclusion Thanks to the technical innovations of the 3rd generation dual-source CTs, the promised lowering of the radiation dose and the quantity of contrast media is achieved with improved image quality. The new CT machines are economically viable over the years.
Keywords: Dual-Source Computertomograph der 3. Generation; Kontrastmittel- und Strahlendosisreduktion; ddc:610